Characteristics of Learners and Their Implications in Learning - Pinton Setya Mustafa (STAI Hubbulwathan Duri, 2022)
The purpose of this article was to provide an informative description of the various characteristics of learning people. The method in this study used a literature study using a qualitative approach through collecting relevant references regarding the diversity of people who learn. This research was a type of literature review research with a qualitative approach. The research procedure consists of: (1) the preparation stage in determining the topic, (2) the implementation stage of searching for relevant reference sources, and (3) the stage of writing down the findings from various reference sources. Reference sources traced in this study come from books and articles that have been published by online journals at 2000-2020. The data analysis stage used in this study was a qualitative approach which includes: data reduction, data presentation, and conclusion. Characteristics of learners can be defined as individual mental factors that can affect learning activities. Multiple intelligence is provided with a special category of intelligence directly for each individual. The conclusion obtained is that every individual who learns is unique in understanding material and information. Therefore, a teacher or educator needs to provide the right model and method to optimize the ability of students to improve their competencies.